Marauder elite intermediate hurdling. A good overview of 400-meter hurdling, with training routines and special drills - Thorson, M. (Track Coach, 2019)
The 400-meter hurdle race for men and women is the most demanding of the hurdle-sprint events. It requires a combination of speed endurance and hurdling skills to go along with a planned and unique stride pattern that demands a very special focus throughout the one-lap race. The race consists of 10 hurdles placed 35 meters apart with a 45-meter run to the first barrier and a 40-meter run-in. The hurdle heights are 91.5 cm (36") for men and 76.0 cm (30") for women. The difficulty in the race comes from a large margin for error which is minimized by adopting and rehearsing a specific race plan that meets all situations.